NixSi1-x Alloys Prepared by Mechanical Milling as Negative Electrode Materials for Lithium Ion Batteries. Issue 2 (29th October 2015) - Du, Zhijia; Ellis, S. N.; Dunlap, R. A.; Obrovac, M. N.
Abstract : Nix Si1-x (0 ≤ x ≤ 0.5, Δx = 0.05) alloys were prepared by ball milling and studied as anode materials for lithium ion batteries. Nanocrystalline Si/NiSi2 phases were formed for x ≤ 0.25. The NiSi phase was observed for samples with higher Ni content. Increasing the Ni content was found to gradually lower the lithiation voltage, while delithiation voltage was not affected for x ≤ 0.25. As a result, Li15 Si4 did not form during cycling for x > 0.15. The capacity trend of Nix Si1-x alloys with composition suggested that the nanocrystalline NiSi2 phase had some activity toward Li, while the NiSi phase had no capacity toward Li. In situ XRD studies confirmed the activity of nanocrystalline NiSi2 . The best cycling performance of Nix Si1-x alloys was obtained for x = 0.20 with 94% capacity retention after 50 cycles.